Refugees and Migrants in Africa: which Status for which Vulnerability? - (:unkn) unknown (My University, 2007)
[International migrations and vulnerabilities] The concept of vulnerability is analyzed in the precarious context of hosting refugee population in Africa. After a quick look at the data, the refugees’ situation is considered in relation with two other types of migration. It is first compared with migrations caused by the fragility of rural communities in Africa; then with migrations related to the crisis of the environment that, following some experts, justify the new concept of “environmental refugees”. Finally, this last question is discussed in the context of the strong tightening of asylum in Europe.
Keywords: African Research